Diurnal variation of the tropospheric water vapour over a coastal and an inland station in Southern Indian Peninsula. (November 2018) - Emmanuel, Maria; Sunilkumar, S.V.; Venkat Ratnam, M.; Muhsin, M.; Parameswaran, K.; Krishna Murthy, B.V.
Abstract: Diurnal variation of atmospheric water vapour in the troposphere over two tropical stations Trivandrum (8.5°N, 76.9°E) and Gadanki (13.5°N, 79.2°E) are studied using radiosonde observations for three years (December 2010–March 2014) carried out as part of Tropical Tropopause dynamics (TTD) campaigns under CAWSES (Climate And Weather of the Sun-Earth System) India Phase II program. Trivandrum is a coastal station and Gadanki an inland station in the Indian Peninsula. Even though the absolute value of columnar integrated water vapour content (IWV) is higher over Trivandrum in all the seasons, the amplitude of its diurnal variation is almost the same (∼± 5–8 kg m −2 ) at both the stations with lower values during the day and higher values during night. Though the absolute humidity decreases exponentially with altitude, the amplitude of normalized diurnal anomaly is more-or-less the same (15–20%) from the surface up to 10 km in all the seasons. There exists a time difference in the peaking hours of water vapour density between the two stations with Gadanki always leading Trivandrum. While the water vapour density maximizes around midnight over Trivandrum, it peaks in the late evening over Gadanki. Harmonic analysis shows that the diurnal and semi-diurnal components together account for almost all the sub-daily variations in IWV and absolute humidity. The contribution of semi-diurnal component is only 25% of that of the diurnal component. Diurnal variation of surface wind speed and direction together with the vertical motion associated with convection regulated by the diurnal variation in temperature seems to play the lead role in causing the diurnal variation in water vapour. While the diurnal variation over Gadanki is mainly controlled by the convectively induced vertical motion, the diurnal variation in the rate of evaporation due to surface wind and local circulation also plays a significant role over Trivandrum. Highlights: Diurnal variation of tropospheric water vapour over Indian peninsula delineated using 3 hourly radiosonde data. The diurnal and semi-diurnal components together could account for almost all the sub-daily variability in water vapour. Local dynamics regulated by the surface temperature causes the diurnal variability in water vapour.